OPTIMASI WAKTU AKTIVASI DAN KARAKTERISASI ARANG AKTIF DARI BATANG TANAMAN GUMITIR DENGAN AKTIVATOR NaOH - Sahara, E.; Resyana, I K. Y.; Laksimawti, A. A. I. A. M. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020, 2020)
The stems of marigold plant can be used as the raw material for making activated carbon. One of the activators that can be used is NaOH with an activated time of 24 hours. The purpose of this study was to obtain an effective activation time through activation with a 2.5% NaOH activator in several variations of activation time followed by characterizing the activated carbon formed. Characterization which was carried out including the determination of water, volatile matter, ash, carbon contents, as well as the absorption capacity of methylene blue and iodine. The results of the study showed that the activation for 28 hours produced an activated carbon with characteristics in accordance with SNI 06-3730-1995, namely: water content (8.40 ± 0.72)%, volatile matter content (9.58 ± 0.95) %, ash content (4.93 ± 0.83)%, carbon content of 77.09%, absorption of iodine (758.66874 ± 1.21) mg/g and absorption of methylene blue 124.6226 mg/g. The results of the analysis with FTIR spectrophotometer on this activated charcoal showed the presence of OH, CH aliphatic, C = O and C = C functional groups.   Keywords: activated carbon, sodium hydroxide, marigold plant stems